Teaching Small Talk: Increasing On-Topic Conversational Exchanges in College Students with Intellectual and Developmental Disabilities Using Remote Audio Coaching. Issue 2 (March 2021) - Joseph, Brianna; Kearney, Kelly B.; Brady, Michael P.; Downey, Angelica; Torres, Ayse
Adults with intellectual and developmental disabilities (IDD) often have deficits in interpersonal skills due to limited social-communication opportunities. Knowing how to engage in "small talk" or simple social conversational exchanges can be beneficial in postsecondary schooling, employment sites, community environments, and social gatherings. Recently, covert audio coaching (CAC) showed a positive impact on increasing conversational exchanges. As the COVID-19 pandemic increased the need for remote delivery tools, we explored the effectiveness of remote audio coaching (RAC) to teach this skill to college students with IDD. We used a multiple baseline design across participants to examine whether RAC might increase on-topic, small talk conversational exchanges. Results demonstrated that RAC effectively increased small talk skills between participants and a confederate. Upon removal of RAC, all participants still performed above their baselines, with two participants maintaining near mastery levels 2 weeks after the intervention was removed. Limitations and future research are discussed.